1999
DOI: 10.1002/(sici)1521-3773(19991216)38:24<3703::aid-anie3703>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Anchoring and Intervesicle Transfer of a Derivative of the Antibiotic Moenomycin A

Abstract: The anchoring of moenomycin A (1) to the bacterial cell cytoplasmic membrane is essential for its biological activity. The first details of the strength of this interaction and the kinetics of the diffusion-mediated intervesicle transfer have been obtained by means of fluorescence spectroscopic methods using a coumarin-labeled moenomycin A derivative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 7 publications
(24 reference statements)
0
23
0
1
Order By: Relevance
“…After lyophilization, pure 2 (16 mg, 64 %) was obtained. 1 H NMR (partly broad signals by micelle formation, [27] Expression and preparation of PBP 1b: The protein was purified from the membrane fraction of E. coli strain JM 109 (K-12 recA1 D(lac-proAB) endA1 gyrA96 thi1 hsdR17 supE44 relA1 F' [tra-D36, proAB , lacI q , lacZDM15]) carrying the plasmid pJP13. This strain expresses the structural gene of PBP 1b of E. coli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After lyophilization, pure 2 (16 mg, 64 %) was obtained. 1 H NMR (partly broad signals by micelle formation, [27] Expression and preparation of PBP 1b: The protein was purified from the membrane fraction of E. coli strain JM 109 (K-12 recA1 D(lac-proAB) endA1 gyrA96 thi1 hsdR17 supE44 relA1 F' [tra-D36, proAB , lacI q , lacZDM15]) carrying the plasmid pJP13. This strain expresses the structural gene of PBP 1b of E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…In the purification process proteins were analyzed by SDS-PAGE and visualized by silver staining and Western blotting with anti-PBP 1b antibodies. For the competition SPR experiments, [26] moenomycin derivative 6 (Scheme 3) [27] was immobilized on a sensor chip surface, which carried N-hydroxysuccinimideactivated carboxylic acid groups.…”
Section: Spr Competition Experimentsmentioning
confidence: 99%
“…The recent description of x-ray crystal structures of the PBP2 extracellular domain from S. aureus (18) and the TG domain of PBP1a from Aquifex aeolicus (19) have provided invaluable structural insights into the plausible mechanism of cell wall peptidoglycan polymerization. Lacking, however, is information regarding the role of the TM domain of PBPs in catalysis, although it has been speculated to interact with the lipid moiety of moenomycin or lipid II (20,21). To address this question, protein constructs containing different domains of PBP1b from Escherichia coli were expressed and purified with suitable detergents [see supporting information (SI) Materials and Methods and SI Fig.…”
Section: Domain Requirement Of Moenomycin Binding To Class a Pbps (Bimentioning
confidence: 99%
“…From structureactivity relationship analysis, it has been found that moenomycin trisaccharides containing the units C, E, F, G, H, and I are the smallest fragments that show antibiotic activity in vivo, whereas moenomycin disaccharides containing the units E-I still act as transglycosylase inhibitors in vitro [3, 7-9, 12, 25]. The isoprenoidlike C 25 -alcohol [26], named moenocinol, seems to be required for the binding of the moenomycin antibiotics to the cytoplasmic membrane [27], whereas the units E, F, and H are concluded to form a polar binding epitope that is recognized by the donor binding site of the transglycosylases [3, 7-9, 19, 28]. In addition to the five known constituents of the Flavomycin complex, structurally related moenomycin-type antibiotics, including the prasinomycins, the diumycins (macarbomycins), ensanchomycin, prenomycin, teichomycin, pholipomycin, AC326-␣, 11837 RP, 8036 RP (quebemecin), and 19402 RP, have been found [3,23,29,30].…”
mentioning
confidence: 99%